Research of the Efficiency Characteristic of Hydro-mechanical CVT - Zhu Zhen; Gao Xiang; Zhu Yu; Pan Daoyuan; Han Meimei (Jixie chuandong)
A hydro-mechanical continuously variable transmission（HMCVT） with a single planetary gear is introduced,and the power transfer of the transmission is analyzed.The efficiency characteristic of transmission is researched from different angles through the definition method and the meshing power method,and the main factors which influence the efficiency of transmission are acquired,the theoretical foundation for the optimization of design scheme and increasement of the transmission efficiency is established.A test bench of hydraulic system is designed,and the main factors which influence the efficiency of hydraulic system are analyzed.A test bench of HMCVT is established,the stepless regulation speed characteristic curves and efficiency characteristic curves are acquired,and the test results are analyzed.